The value of top-down communication for organizational performance - Leif Brandes; Donja Darai (University of Zurich, Department of Economics, 2014)
We design a laboratory experiment to identify causal performance effects of top-down communication between managers and their subordinates. Our focus lies on communication that resolves uncertainty about the work environment but does not provide task-specific knowledge. Recent articles in the business press report a lack of such communication in real-world organizations and associate it with reduced organizational performance. Our results confirm this observation. We find that top-down communication is a profitable way for managers to increase employee performance in the presence of uncertainty. Specifically, we show that non-communication is the worst option for managers. However, 50 percent of our experimental managers use top-down communication too restrictively. Overall, managers forego 30 percent of their potential profits through non-communication. We show that organizations can overcome this problem by adopting automated information procedures, which are equally effective.
Keywords: C92; D23; D83; M54; 330; communication procedures; non-instrumental-information; employee motivation